PAI Teacher Competence Concept of Ayyuhal Walad Perspective - Ashif Az Zafi; Muhammad Shidqul Wafa (PALAPA, 2021)
The purpose of this study is to describe the concept of PAI teacher competence, propose the concept of PAI teacher competence from the perspective of the Ayyuhal Walad book and analyze the implications of the impact of the PAI teacher competence concept in the Ayyuhal Walad book. This research is included in the library research method by collecting, citing and analyzing using data collection analysis from the literature that is representative and relevant to the discussion. The results of this study indicate that the concept of teacher competence is dominated by the competence of the teacher's personality.